KONSENTRASI IAA (Indole Acetic Acid) DAN BAP (Benzyl Amino Purine) PADA KULTUR JARINGAN ULIN (Eusideroxylon zwageri) - Wahyuni, Herni; Wulandari, Reine Suci; muflihati, Muflihati (Universitas Tanjungpura, 2019)
Ulin (Eusideroxylon zwageri) is a species of wood with high economic value that is difficult to find in the wild. Regeneration of E. zwageri is naturally very slow. Efforts to increase the procurement of E. zwageri seedlings can be done with a tissue culture technique. Through tissue culture, the seeds obtained will be uniform, have better quality and faster. This study aims to determine the effect and optimum concentration of IAA and BAP growth regulators on E. zwageri explants growth. The method used is experimental using a completely randomized design. Treatment factors are IAA concentration factor with 5 levels of treatment (0 mg/L, 0.5 mg/L, 1 mg/L, 1.5 mg/L, and 2 mg/L) and BAP concentration of 5 treatment levels (0 mg/L, 1 mg/L, 2 mg/L, 3 mg/L, and 4 mg/L). Each treatment was repeated 3 times. The results showed that the treatment of IAA concentration, BAP concentration and the interaction of IAA and BAP concentration affected the swelling of explants and growth of E. zwageri callus. The best concentration for callus explants was IAA of 2 mg/L and BAP of 0 mg/L, with a time of 12-13 weeks after planting.Keywords: BAP, E. zwageri, IAA, Tissue Culture